2014
DOI: 10.1371/journal.pone.0106615
|View full text |Cite
|
Sign up to set email alerts
|

Coordination in Fast Repetitive Violin-Bowing Patterns

Abstract: We present a study of coordination behavior in complex violin-bowing patterns involving simultaneous bow changes (reversal of bowing direction) and string crossings (changing from one string to another). Twenty-two violinists (8 advanced amateurs, 8 students with violin as major subject, and 6 elite professionals) participated in the experiment. We investigated the influence of a variety of performance conditions (specific bowing patterns, dynamic level, tempo, and transposition) and level of expertise on coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 71 publications
(106 reference statements)
0
18
0
Order By: Relevance
“…Recently, however, there is an increased interest in complex natural movements as a source for understanding motor organization. Above all, this concerns studies of the movements of the arm playing musical instruments (Winold et al, 1994;Turner-Stoker and Reid, 1999;Rasamimananal et al, 2007;Furuya and Kinoshita, 2008;Bril and Goasdoué, 2009;Furuya et al, 2009Furuya et al, , 2011Kazennikov and Wiesendanger, 2009;Konczak et al, 2009;Verrel et al, 2013a,b;Schoonderwaldt and Altenmüller, 2014). This research was partly fueled by the necessity to study professional pathologies of musicians and to develop relevant therapeutic methods (Bragge et al, 2006;Kelleher et al, 2013).…”
Section: Post-bernsteinian "Bottom-up" Studies Of Complex Natural Movmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, however, there is an increased interest in complex natural movements as a source for understanding motor organization. Above all, this concerns studies of the movements of the arm playing musical instruments (Winold et al, 1994;Turner-Stoker and Reid, 1999;Rasamimananal et al, 2007;Furuya and Kinoshita, 2008;Bril and Goasdoué, 2009;Furuya et al, 2009Furuya et al, , 2011Kazennikov and Wiesendanger, 2009;Konczak et al, 2009;Verrel et al, 2013a,b;Schoonderwaldt and Altenmüller, 2014). This research was partly fueled by the necessity to study professional pathologies of musicians and to develop relevant therapeutic methods (Bragge et al, 2006;Kelleher et al, 2013).…”
Section: Post-bernsteinian "Bottom-up" Studies Of Complex Natural Movmentioning
confidence: 99%
“…Participants in these studies were music players of different levels of skill, from beginners to amateurs to professionals. Researchers examine the adaptation of joint coordination to various conditions of performance, including tempo (Winold et al, 1994;Rasamimananal et al, 2007;Furuya et al, 2011;Schoonderwaldt and Altenmüller, 2014), sound power (Furuya and Kinoshita, 2008;Furuya et al, 2009;Schoonderwaldt and Altenmüller, 2014), type of instrument (Turner-Stoker and Reid, 1999;Bril and Goasdoué, 2009), and character of partition (Winold et al, 1994). The abovementioned works demonstrate efficiency of "bottom-top" approach for the analysis of the differences in the level of skills, in both kinematic and dynamic aspects of the organization of movement.…”
Section: Post-bernsteinian "Bottom-up" Studies Of Complex Natural Movmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustained bowing gestures may not provide as clear an indication of note onsets as the striking actions used in piano performance, rendering visual cues from violinists less informative than visual cues from pianists. For instance, study of violinists’ bowing gestures has shown that changes in bow direction lag behind string transitions as performers move between notes ( Schoonderwaldt & Altenmüller, 2014 ), potentially enhancing the ambiguity of observed note onsets. Violinists’ audio cues may be less informative as well.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some instrumentalists need to produce phase shifted movements with different limbs due to the physical setup of their instrument. This is for example the case on the violin where a string has to be pushed down with the left hand before the bow is moved or the string is plugged with the right hand [22]. Pipe organs, another example, can exhibit delays of up to 150 ms [23] that vary according to pitch and may vary for different manuals and pedals.…”
Section: Introductionmentioning
confidence: 99%